Penyuluhan Fisioterapi Upaya Pencegahan dan Penanganan Awal Cedera Pergelangan Kaki pada Komunitas Olahraga Lansia Pakis Kembar - Lukmanul Hakim; Arys Hasta Baruna (Health Care : Journal of Community Service, 2024)
Community physiotherapy is one form of physiotherapy approach in improving understanding of health and maintaining body movement function among the community. Sports have a major impact on survival, this kind of activity can benefit many things, especially in improving physical quality, helping to develop the brain and emotional stabilization. In East Java, lower limb injuries were found to be 54.2%, and the type of sprain or dislocation injury was 40.1%. Ankle sprain is one of the musculoskeletal injuries that is often experienced by most people when doing activities or exercising. To overcome this, you can do strengthening with several exercises that focus on the ankle and first aid using the PRICE method as first aid. This counseling had 28 participants. The method used was to provide physiotherapy counseling that focused on strengthening and handling ankle injuries with posters and leaflets. The results obtained before and after the presentation of the material, there was an increase in understanding about strengthening and handling ankle injuries in the Lanisa Pakis Kembar sports community.